2012
DOI: 10.1111/j.1751-2980.2012.00593.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, clinical manifestations and endoscopic features of eosinophilic esophagitis: A pathological review in China

Abstract: OBJECTIVE:  We aimed to determine the prevalence of eosinophilic esophagitis (EoE) and define its clinical and endoscopic characteristics in Chinese patients. METHODS:  Esophageal specimens obtained from January 2006 to December 2010 in the First Affiliated Hospital of Sun Yat‐sen University were reviewed, and the data on clinical characteristics and endoscopic findings of patients were obtained. Patients with eosinophils ≥15 per high power field (HPF) were identified as having EoE. RESULTS:  A total of 12 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 22 publications
(47 reference statements)
0
31
0
3
Order By: Relevance
“…(8,17) To date, only a few studies have reported the prevalence of EoE in Chinese or Asians, most of which were conducted in adult Asian populations. (5,6) The condition affects not only adult populations, but also paediatric populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(8,17) To date, only a few studies have reported the prevalence of EoE in Chinese or Asians, most of which were conducted in adult Asian populations. (5,6) The condition affects not only adult populations, but also paediatric populations.…”
Section: Discussionmentioning
confidence: 99%
“…However, while EoE is a well-recognised disease in the West, there is little epidemiological data on EoE from nonWestern countries, such as China, Korea and Saudi Arabia. (5)(6)(7) The diagnosis of EoE is predominantly dependent on the patient's clinical presentation, and the endoscopic and histologic findings of mucosal biopsies taken from the oesophagus. Although eosinophil count is used in EoE diagnosis, it is not considered to be the gold standard for EoE diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Based on recent studies, the prevalence of EoE is lower in Asia with reported rate 0.34% in China [25] and 0.02% of the routine endoscopies in Japan [26] . In adults with EoE, solid food dysphagia is the most common presenting symptom, followed by food impaction.…”
Section: Complications No Complicationsmentioning
confidence: 99%
“…EoE has become increasingly prevalent over the past decade, especially in Western countries [3,4]. While the epidemiology of EoE has not been fully evaluated, it appears that the incidence and prevalence of EoE and esophageal eosinophilia (EE) are also increasing in Asian countries, including Japan [5,6,7,8]. Pathologically, the hallmark of EoE is EE, commonly defined by more than 15 eosinophils per high power field (HPF) in at least 1 esophageal biopsy specimen.…”
Section: Introductionmentioning
confidence: 99%